PROSPECTS OF RUSSIA CONSTRACTION INDUSTRY - I. Kostyrina (Вестник университета)
Аnnotation. The article discusses prospects of industry development in actual economic conditions. Development problems of the investment and construction complex and building material industry were detected. In addition the more interesting areas for investing were indicated. Practical recommendations for implementation of import programs in construction industry were also provided for development of the most prospective areas in building materials industry, technological structure of capital investments were also represents.